2012
DOI: 10.1002/ajhb.22256
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in body composition for children and young adults: The fels longitudinal study

Abstract: Objectives To determine secular trends by birth decade in body mass index (BMI), waist circumference/height (W/Ht), percent body fat (PBF), and fat free mass adjusted for height squared (FFM/Ht2) in children and adolescents aged 8–18 years. Methods Serial data were analyzed from 628 boys and 591girls aged 8 to 18 years who participated in the Fels Longitudinal Study. Subjects were stratified by birth decade from 1960 through 1999. Means and standard deviations were computed for all measurements by birth deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 40 publications
1
32
0
1
Order By: Relevance
“…There is very little evidence with respect to secular trends in fat-free mass. In children and adolescents, a study (Sun et al, 2012) conducted in the US found that fatfree mass (adjusted for height) was lower in boys born in the 1990s than in boys born in the 1960s, 1970s or 1980s, but there was no secular trend on this measure in girls. (According to Malina (2004), height in children in the US increased very slightly and only at the 5th and 10th percentiles, between 1963-1994; thus the adjustment for height should not have affected the across-time comparisons of fat-free mass in the study by Sun et al) For adults, the only data available are for US Army recruits (Sharp et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…There is very little evidence with respect to secular trends in fat-free mass. In children and adolescents, a study (Sun et al, 2012) conducted in the US found that fatfree mass (adjusted for height) was lower in boys born in the 1990s than in boys born in the 1960s, 1970s or 1980s, but there was no secular trend on this measure in girls. (According to Malina (2004), height in children in the US increased very slightly and only at the 5th and 10th percentiles, between 1963-1994; thus the adjustment for height should not have affected the across-time comparisons of fat-free mass in the study by Sun et al) For adults, the only data available are for US Army recruits (Sharp et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Details of FLS participants and data collection process have been reported previously (16, 20). All FLS participants have been monitored since birth and have had serial measures of stature and weight taken at one, three, six, nine and 12 months, then semi-annually to 18 years, and biennially thereafter.…”
Section: Methodsmentioning
confidence: 99%
“…DXA was measured through Hologic ™ QDR 4500 Elite densitometer (Hologic, Waltham, MA) and a Lunar LPX machine. The calibration of the measurement and conversion between the Hologic and Lunar DXA machines were described in detail formerly (20). The number of DXA measurements and ages at which repeated DXA measurements were made vary and depend on the age of a participant when DXA measurements were introduced into FLS; age when the minimum weight was required for measurement of DXA; and whether annually scheduled examinations were missed.…”
Section: Methodsmentioning
confidence: 99%
“…A recent paper (Sun et al 2012) examined trends in body composition in children born between 1960–1999 in the Fels Longitudinal Study (Roche 1992). Differences in mean BMI, percentage body fat (%fat) and a fat-free mass index (FFMI = fat-free mass/height 2 ) between birth year decades were tested within yearly chronological age groups; a trend in increasing BMI and %fat was observed in the absence of a trend in increasing FFMI.…”
Section: Introductionmentioning
confidence: 99%
“…552). To ameliorate this issue, the recently published paper (Sun et al 2012) used conversion equations to adjust the hydrodensitometry values to obtain similar means to the DXA values, but these equations have not been validated in any publication. The concern over pooling data from two different methods which were implemented over different periods of the study is that assessment of secular trends may be biased by the known intra-method differences.…”
Section: Introductionmentioning
confidence: 99%